Efektivitas Pembelajaran PAK Secara Luring di Tengah Pandemi Covid-19 - Semuel Selanno; Orient Christianty (Jurnal Ilmiah Wahana Pendidikan, 2021)
The study aims to find out and explain how the effectiveness of Christian religious education is offline amid the covid-19 pandemic at the pinamorongaan Christian junior high school. The learning problems that occur in this school are matters that must be dealt with seriously because these learning effectiveness issues have a major impact on students because when learning does not go as expected, it is achieving the educational goals where students can understand and understand the existing learning materials. The methods used in descriptive qualitative research. , images or recordings, with definite data criteria. The informers in the study included 11 people-10 students and 1 teacher in Christian education. Based on the results of the study, it was found that learning ineffective to take offline the study of Christian religious education amid the covid-19 pandemic at the pinamination Christian junior high school. This is because Christian teachers of education, who have never conducted good classes, are unable to make the appropriate maximize of time during the spread of this disease and also cannot use the proper methods of learning offline in the new normal era.